CHALLENGES AND TRENDS OF BUILDING NEW WORLD ARCHITECTURE WITH BRICS+ COUNTRIES - Kharitonova, Yulia S.; Belitskaya, Anna V. (International Journal of Law in Changing World, 2025)
BRICS is a unique multilateral organization spanning Europe, Latin America, Asia, and Africa, playing a key role in shaping a multipolar world. The expanded BRICS+ holds transformative potential by creating alternatives to dominant global systems, such as international currency, the World Bank, and ICSID arbitration. This paper proposes a diversified approach to support member states in achieving synergy for shared economic growth. To reach this goal, the authors applied comparative legal analysis, formal legal methods, retrospection, and legal forecasting. A core finding highlights the need to harmonize key areas of legislation across BRICS+ members—especially antitrust, customs, financial regulation, and investment dispute resolution. Establishing favorable conditions for business partnerships is essential. The paper identifies priority sectors for cooperation—energy, security, innovation, trade, digital transformation, and financial markets—as the foundation for joint development of balanced policies. These efforts aim to align business, antitrust, and investment frameworks, fostering deeper integration and collaboration within the BRICS+ alliance. _____ RETOS Y TENDENCIAS PARA LA CONSTRUCCIÓN DE UNA NUEVA ARQUITECTURA MUNDIAL CON LOS PAÍSES BRICS+ El BRICS es una organización multilateral única que abarca Europa, América Latina, Asia y África, y desempeña un papel clave en la configuración de un mundo multipolar. El BRICS+ ampliado posee un potencial transformador al crear alternativas a los sistemas globales dominantes, como la moneda internacional, el Banco Mundial y el arbitraje del CIADI. Este documento propone un enfoque diversificado para apoyar a los Estados miembros en el logro de sinergias que fomenten un crecimiento económico compartido. Para alcanzar este objetivo, los autores aplicaron análisis jurídico comparativo, métodos jurídicos formales, retrospección y previsión jurídica. Un hallazgo fundamental destaca la necesidad de armonizar áreas clave de la legislación entre los miembros del BRICS+, especialmente las leyes antimonopolio, aduaneras, regulación financiera y resolución de disputas de inversión. Establecer condiciones favorables para las alianzas comerciales es esencial. El documento identifica sectores prioritarios para la cooperación —energía, seguridad, innovación, comercio, transformación digital y mercados financieros— como base para el desarrollo conjunto de políticas equilibradas. Estos esfuerzos buscan armonizar los marcos comerciales, antimonopolio y de inversión, fomentando una mayor integración y colaboración dentro de la alianza BRICS+. _____ 与“金砖国家+”共建新世界格局的挑战与趋势 金砖国家是一个独特的多边组织，横跨欧洲、拉丁美洲、亚洲和非洲，在塑造多极世界方面发挥着关键作用。扩大后的“金砖国家+”拥有变革潜力，能够为国际货币、世界银行和国际投资争端解决中心（ICSID）等主流全球体系创造替代方案。本文提出了一种多元化的方法，以支持成员国实现协同增效，实现共同经济增长。为了实现这一目标，作者运用了比较法律分析、正式法律方法、回顾和法律预测。一项核心发现强调了协调“金砖国家+”成员国关键立法领域的必要性，尤其是在反垄断、海关、金融监管和投资争端解决方面。为商业伙伴关系创造有利条件至关重要。本文确定了合作的重点领域——能源、安全、创新、贸易、数字化转型和金融市场——作为共同制定平衡政策的基础。这些努力旨在协调商业、反垄断和投资框架，促进金砖国家+联盟内部更深层次的融合与合作。